Measurement of the ratio of inclusive cross sections sigma(p(p)over-bar -> Z plus b-quark jet)/sigma(p(p)over-bar -> Z plus jet) at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Weber, M.; et al. (Amer Physical Soc, 2011)
The ratio of the cross section for p (p) over bar interactions producing a Z boson and at least one b-quark jet to the inclusive Z + jet cross section is measured using 4.2 fb(-1) of p (p) over bar collisions collected with the D0 detector at the Fermilab Tevatron collider at root s = 1.96 TeV. The Z -> l(+) l- candidate events with at least one b jet are discriminated from Z + charm and light jet(s) events by a novel technique that exploits the properties of the tracks associated to the jet. The measured ratio is 0: 0193 +/- 0: 0027 for events having a jet with transverse momentum p(T) > 20 GeV and pseudorapidity vertical bar eta vertical bar <= 2.5, which is the most precise to date and is consistent with theoretical predictions.